ANALISIS PENGARUH KINERJA UMKM, KEPERCAYAAN DAN PERSEPSI RISIKO TERHADAP NIAT INVESTASI PADA UMKM MELALUI PLATFORM EQUITY CROWDFUNDING DI INDONESIA - Aprihasyyati, Dalilatiyani Ajrinatia; Fitria, Shoimatul (Diponegoro Journal of Management, 2020)
Investment in MSME through the Equity Crowdfunding Platform was introduced and implemented in Indonesia at the end of 2018. The number of investors and investment value on the Equity Crowdfunding platform in Indonesia until 2019 experienced a drastic increase where the percentage increase was more than 100%. However, research related to Equity Crowdfunding in Indonesia has not been done much. This study has a general objective to analyze the effect of MSME performance, trust and risk perception on investment intentions at MSME through the Equity Crowdfunding Platform in Indonesia.The population used in this study are investors of the Equity Crowdfunding Platform in Indonesia. The sample used was 144 respondents. The sample collection method used was purposive sampling. The data collection methods were used questionnaires. This research uses Structural Equation Modeling (SEM) analysis with AMOS 24.0 analysis tools.The results of this study indicate that the performance of MSMEs has a positive and significant effect on trust and investment intentions. Then, trust has a positive and significant effect on investment intentions. While trust has a negative and significant effect on risk perceived. In addition, risk perceived also has a negative and significant effect on investment intentions. Trust variables are found to have a dominant influence on investment intentions so it is important for company managers to be able to maintain and even increase investor’s trust by building a systematic evaluation mechanism.